The criminal crowd and other writings on mass society - Sighele, Scipio (The Lorenzo Da Ponte Italian library, 2018)
"The Criminal Crowd and Other Writings on Mass Society is the first English collection of writings by Italian jurist, sociologist, cultural and literary critic Scipio Sighele. Sighele is largely responsible for providing post-unification Italy with a new outlook on issues ranging from the blurring line between individual and collective accountability, the role of urbanization in the development of criminality, and the emancipation of women. This work draws a multifaceted portrait of a provocative thinker and public intellectual caught between tradition and modernity during the European fin de siècle. Containing a comprehensive introduction by the editor, The Criminal Crowd and Other Writings on Mass Society includes Sighele's seminal work, The Criminal Crowd, as well as his formative studies on group behaviour. Nicoletta Pireddu contextualizes Sighele's contribution to the so-called 'age-of crowds,' from the fierce polemic with his French rivals Gustave LeBon and Gabriel Tarde to the scientific, literary, and cultural developments of his conceptualization of mass behaviours as a legitimate object of psychological investigation into a new century."--